2022
DOI: 10.1097/jxx.0000000000000706
|View full text |Cite
|
Sign up to set email alerts
|

Home-based primary care visits by nurse practitioners

Abstract: Background: With rapidly growing numbers of homebound older adults, the need for effective home-based health interventions is increasingly recognized. Advanced practice registered nurses (NPs) are one of the most common providers of home-based primary care. Limited information is available to address the scope and nature of NP-led home-based primary care and associated outcomes.Objective: To synthesize research evidence of NP visits in home-based primary care.Data Sources: Six electronic databases-PubMed, Cumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Due to the inability to differentiate between hospitalizations and ED transfers in the extracted data, they were treated as a combined dependent (outcome) variable. This choice was supported by previous research that has treated these variables separately or combined 30,35 . Independent variables encompassed patient‐related variables, patient‐related events, and setting‐related variables 33,34,36 .…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…Due to the inability to differentiate between hospitalizations and ED transfers in the extracted data, they were treated as a combined dependent (outcome) variable. This choice was supported by previous research that has treated these variables separately or combined 30,35 . Independent variables encompassed patient‐related variables, patient‐related events, and setting‐related variables 33,34,36 .…”
Section: Methodsmentioning
confidence: 94%
“…Hospitalizations and ED transfers were significantly reduced when PHCNP provided planned interventions. Although other countries have integrated PHCNPs into these teams, 30,35 few studies have examined the effect of this practice on hospitalization and transfer of people to the ED. Since one of the objectives of home care provision is to reduce the number of in-patient admissions and ED transfers where possible, 46,47 our results add to understanding whether the addition of PHCNPs to home care teams is an effective solution for meeting healthcare needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These indicators were categorized into health, cardiovascular, cancer care, diabetes, mental health, renal, respiratory, rheumatoid arthritis outcomes. Each one is detailed below: a. Clinical/Health outcomes were found in eight studies [12,35,36,41,42,47,53,57,58] and included health risk reduction, health status, self-reported perceived health, SF 36 physical composite score, physiologic measures, and clinical outcomes. Milesky et al [47] reported that NPs improved health outcomes in almost one fifth of theme occurrences.…”
Section: Patient Indicator Categoriesmentioning
confidence: 99%
“…g. Clinical/Respiratory outcomes were outlined in six reviews [27,29,33,35,36,53,60]. No significant differences were noted between the intervention and control groups for change in maximal peak flow in asthma, emergency nebulization, frequency of exacerbation, 6-month follow-up, asthma severity, asthma symptoms, absence from school or work due to asthma, forced expiratory volume at one second (FEV1), peak flow rate, airway hyperreactivity using PD/PC20 methacholine/histamine, as well as lung function at 12 h. Clinical/Rheumatoid arthritis outcomes were noted in two studies [56,59].…”
Section: Plos Onementioning
confidence: 99%